2007
DOI: 10.1227/01.neu.0000255336.80285.70
|View full text |Cite
|
Sign up to set email alerts
|

An Astroblastoma Mimicking a Cavernous Malformation

Abstract: A rare radiological to pathological correlation of astroblastoma is presented in which the evolving hematoma, as observed on magnetic resonance imaging scans, complicated the radiographic diagnosis of this lesion. The clinical, radiographic, and pathological features of astroblastomas, as well as the natural history of these rare glial neoplasms, are reviewed. This case illustrates the capacity of astroblastomas to hemorrhage, disguising the classic radiographic findings typical of this glial neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…These features resemble a CCM. This case together with other reports [10][11][12][13][14] might suggest an oncogenetic feature of glioblastoma. This indicates that some gliomas may develop from CCM.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These features resemble a CCM. This case together with other reports [10][11][12][13][14] might suggest an oncogenetic feature of glioblastoma. This indicates that some gliomas may develop from CCM.…”
Section: Discussionsupporting
confidence: 84%
“…This indicates that some gliomas may develop from CCM. Recently, many reports [10][11][12][13][14][15][16][17] have indicated that there may be a relationship between CCM and intracranial tumors such as glioma, meningioma, and schwannoma. There also have been some reports of glioblastoma presenting as suspected arteriovenous malformation [1,10] .…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic appearance is not uncommon; there are three reported cases in which radiologic presentation was confused with vascular etiologies because the initial presentation was acute hemorrhage. [12231] Differential diagnoses in imaging are ependymoma, primitive neuroectodermic tumor, and atypical rhabdoid-teratoid tumor. [4]…”
Section: Discussionmentioning
confidence: 99%
“…Acute hemorrhage as the initial presentation of astroblastoma is a rare occurrence [12]. Brain tumors in general are an uncommon cause of acute brain hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Primary brain tumors such as glioblastoma and anaplastic astrocytoma may also be associated with brain hemorrhage, although less frequently than metastatic lesions [14]. Only one previous report has described hemorrhage in association with astroblastoma (low-grade), which was initially thought to be a cavernous malformation based on imaging studies [12]. As mentioned earlier, the patient in this report experienced significant postoperative complications including venous thromboses in both the upper and lower extremities prompting low-dose heparin therapy and the insertion of an inferior vena cava filter.…”
Section: Discussionmentioning
confidence: 99%